2002
DOI: 10.1177/056943450204600203
|View full text |Cite
|
Sign up to set email alerts
|

Who's Afraid of Their Economics Classes? Why are Students Apprehensive about Introductory Economics Courses? An Empirical Investigation

Abstract: This paper investigates why students are apprehensive about their principles of economics classes. Using data collected on 399 students from a large, midwestem public university in the 1998 academic year, the authors examine whether there are demographic differences in levels of apprehension and what are the reported reasons for apprehension. The study includes a descriptive analysis and a probit analysis and concludes that: (1) course reputation is the main reason reported by students as the reason for being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…to measure student attitudes as a result of exposure to economics instruction" (Soper & Walstad, 1983, p. 5). As with STEM education, the emphasis has been on measuring attitudes toward the study of economics (e.g, see, Benedict & Hoag, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…to measure student attitudes as a result of exposure to economics instruction" (Soper & Walstad, 1983, p. 5). As with STEM education, the emphasis has been on measuring attitudes toward the study of economics (e.g, see, Benedict & Hoag, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Benedict and Hoag (2002) examined the effect of student-level characteristics, questionnaire data, and enrollment in introductory microeconomics or macroeconomics on students’ course-related apprehension. The authors found students’ mathematical proficiency as measured by ACT Math score had a negative and significant effect on the probability of student apprehension.…”
Section: Program Designmentioning
confidence: 99%
“…They find that the greatest gain is achieved by those in the lower part of the student performance distribution. Further connections as to why math skills are important have been link to the reduction of anxiety that interferes with the learning process in introductory economic courses, see Benedict & Hoag (2002). 6.…”
Section: Notesmentioning
confidence: 99%